Electricity retailing in Norway - Nils-Henrik M. von der Fehr; Petter Vegard Hansen (University of Oslo, Department of Economics, 2009)
We analyse retailer and household behaviour on the Norwegian electricity market, based on detailed information on prices and other market characteristics. We find that there exists a competitive market segment where a number of retailers compete fiercely for customers, with small margins on all products. However, we also find evidence of monopolistic behaviour, whereby retailers exploit the passivity of some of their customers. We discuss explanations for these results, as well as means to improve market performance.
Keywords: 330; Elektrizitätswirtschaft; Deregulierung; Wettbewerb; Betriebliche Preispolitik; Norwegen